Red-shifted and pH-responsive imidazole-based azo dyes with potent antimicrobial activity. Issue 19 (15th February 2023) - Dantas, Daniela; Ribeiro, Ana I.; Carvalho, Filipe; Gil-Martins, Eva; Silva, Renata; Remião, Fernando; Zille, Andrea; Cerqueira, Fátima; Pinto, Eugénia; Dias, Alice M.
Abstract : A novel route is described to obtain antimicrobial 2-aminoimidazole azo dyes with a unique substituent pattern in the heteroaryl unit that provides halochromic properties, exhibiting vibrant colours that change from magenta to deep blue. Abstract : A novel route is described to obtain 2—aminoimidazole azo dyes with a unique substituent pattern in the heteroaryl unit that provides halochromic properties, exhibiting vibrant colours that change from magenta to deep blue. Potent antimicrobial properties against infectious yeasts were demonstrated. No cytotoxicity was detected for concentrations lower than 16 μg mL −1 .